On-the-job search and optimal schooling under uncertainty and irreversibility - Anna Zaharieva (Bielefeld University, Center for Mathematical Economics (IMW), 2013)
This paper develops a labour market model with on-the-job search, match-specific productivity draws and an endogenous irreversible schooling decision. The choice of schoolin is modelled as an optimal stopping problem which gives rise to the equilibrium heterogeneity of workers with respect to the formal education. The optimal schooling decision is characterized by the reservation productivity of students which is a monotonic function of time. Moreover, this reservation productivity is lower in expansions when job-to-job mobility is more intensive. Therefore, the model is compatible with the empirical evidence that expansions have a positive effect on the probability of a school dropout. The schooling density is downward-sloping and the equilibrium wage distribution is right-skewed with a unique interior mode. This means that the majority of workers earn wages in the middle range of the earnings distribution. At the same time there is a small proportion of employees in the beginning of their career with wages in the left tail of the earnings distribution and a small proportion of high-skilled workers earning wages in the right tail of the distribution.
urn:nbn:de:0070-pub-27007123
Keywords: I21; I24; J62; J64; 330; Optimal schooling; uncertainty; on-the-job search; wage dispersion